Investigating printability and buildability of 3D printed cementitious materials - Goh, Jia Hui (Nanyang Technological University, 2020)
This report investigates how various admixtures affect the printability and buildability of 3D printed cementitious materials. The ability for mixture to extrude from the nozzle smoothly without discontinuities or cracks is defined as printability; whilst the ability to sustain printed layers above the bedding layers, without deforming or collapsing is defined as buildability. Flow rate coupled with surface quality are used as a parameter to quantify printability; whilst number of layers of building height are quantified for buildability. Recycled glass was used as fine aggregate in mortar mixtures instead of river sand; whilst nanoclay and polycarboxylate ether superplasticizer (PCE) were used as admixtures to the ordinary Portland cement concrete in different ratios. Recycled glass is selected due to its inert and non-biodegradable properties which is detrimental for the environment; whilst nanoclay and PCE are selected for its ability to enhance the rheological properties. The static yield stress and dynamic yield stress of individual mixture designs were determined using the stress growth and step-down protocol, respectively. Results from the rheological properties obtained were validated by conducting actual 3D printing to determine the printability, buildability and interlayer bonding tensile strength. A preliminary study found that the utilization of recycled glass in 3D printed mortar results in low static yield stress, which lowers the thixotropy. Thixotropic ratio is a measure of static yield stress over dynamic yield stress. It has been observed that static yield stress is related to buildability, whilst dynamic yield stress is related to printability. In this investigation, nanoclay and PCE were used to enhance the thixotropy and, consequently printability and buildability. It was found that the mixture of both PCE and nanoclay in recycled glass mortar resulted in high thixotropic ratio which is ideal in 3D concrete printing (3DCP) applications.